2018
DOI: 10.1038/s41566-018-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

Opto-thermoelectric nanotweezers

Abstract: Optical manipulation of plasmonic nanoparticles provides opportunities for fundamental and technical innovation in nanophotonics. Optical heating arising from the photon-to-phonon conversion is considered as an intrinsic loss in metal nanoparticles, which limits their applications. We show here that this drawback can be turned into an advantage, by developing an extremely low-power optical tweezing technique, termed opto-thermoelectric nanotweezers (OTENT). Through optically heating a thermoplasmonic substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
309
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 247 publications
(331 citation statements)
references
References 39 publications
1
309
0
1
Order By: Relevance
“…It is important to note that by contrast to standard nanotweezing schemes, all examples in Figure use much lower laser powers (a few mW or less) to manipulate and assemble nanostructures. In this context, recently Lin et al showed that thermophoresis can also be used to sculpt structures into versatile shapes by selectively manipulating individual particles of different material compositions, sizes and shapes …”
Section: Heating Up the Environmentmentioning
confidence: 99%
“…It is important to note that by contrast to standard nanotweezing schemes, all examples in Figure use much lower laser powers (a few mW or less) to manipulate and assemble nanostructures. In this context, recently Lin et al showed that thermophoresis can also be used to sculpt structures into versatile shapes by selectively manipulating individual particles of different material compositions, sizes and shapes …”
Section: Heating Up the Environmentmentioning
confidence: 99%
“…Moreover, the fiber‐based trapping scheme is readily integrated with other optical systems to extend the manipulation from 2D to 3D. Recently, thermophoresis‐induced optical manipulation and assembling techniques have been extensively studied by Zheng and co‐workers via particle surface modification and surface entropy tuning …”
Section: Thermal Optofluidic Applicationsmentioning
confidence: 99%
“…Using a customized particle‐surface modification process, Lin et al recently developed optothermoelectric nanotweezers, which exploit the electrolyte Seebeck effect to manipulate metallic particles . A cationic surfactant, cetyltrimethylammonium chloride (CTAC), was used to modify the particle surfaces.…”
Section: Thermal Optofluidic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the use of high NA lens, high laser power, and complex optical setup in optical tweezers makes them difficult to use for large‐scale and widespread applications in digital manufacturing. To overcome these challenges, opto‐thermophoretic tweezers have been developed to trap and manipulate particles of a wider range of sizes, shapes, and compositions using low optical power . Opto‐thermophoretic tweezers provide an opportunity for nanoparticle assembly and printing, thus enhancing the field of nanoscale manufacturing.…”
Section: Opto‐thermophoretic Tweezers For Nanomanufacturingmentioning
confidence: 99%